2022
DOI: 10.1039/d2ra06139b
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic dependence of radiation from excitons in Ga2O3/MoS2heterostructure

Abstract: The anisotropic dependence of radiation arising from exciton recombination in the Ga2O3/MoS2 heterostructure is investigated, using density functional theory and the Bethe–Salpeter equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Comparing Eqs. (3,4) and (5,6), we notice that if the incident light propagates in plane, the Raman intensity is independent of the angle of incident light (f). However, when the incident light propagates out of plane, the Raman intensity depends on the angle of the incident light, and we will discuss this point in the next sections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing Eqs. (3,4) and (5,6), we notice that if the incident light propagates in plane, the Raman intensity is independent of the angle of incident light (f). However, when the incident light propagates out of plane, the Raman intensity depends on the angle of the incident light, and we will discuss this point in the next sections.…”
Section: Methodsmentioning
confidence: 99%
“…Selenium nanostructure-based semiconductors have a variety of potential applications in the fabrication of many highperformance devices. [1,2] Among them, as the family member of group III monochalcogenides (GaS, GaSe, InS, and InSe), few layers InSe have received a lot of interest, [3][4][5] due to the excellent carrier mobility, abnormal magneto-optic effect, [6] efficiency of splitting water, [7,8] thermal conductivity and significant band gap tunability. Recently, two-dimensional (2D) fewlayer InSe has been successfully synthesized, and exhibits good photothermal conversion efficiency, [3,[9][10][11][12][13][14][15][16][17] high mobility, improved exciton dissociation, decreased charge recombination, optical properties, [18] improved light harvesting, [19] and potential applications of multilayer InSe flake based FETs, [20] compared to other 2D materials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in 2023, Leblanc et al reported a WS 2 /Ga 2 O 3 heterostructure with a rectification ratio up to 10 6 . Despite significant progress being made in device development, the band alignment and interlayer carrier transfer mechanism of a variety of TMDs/Ga 2 O 3 heterostructures still needs in-depth exploration, particularly with regard to the direct observation of their broadband absorption spectra through experimental methods. …”
Section: Introductionmentioning
confidence: 99%